2012
DOI: 10.1007/s12402-012-0086-2
|View full text |Cite
|
Sign up to set email alerts
|

ADHD and autism: differential diagnosis or overlapping traits? A selective review

Abstract: According to DSM-IV TR and ICD-10, a diagnosis of autism or Asperger Syndrome precludes a diagnosis of attention-deficit/hyperactivity disorder (ADHD). However, despite the different conceptualization, population-based twin studies reported symptom overlap, and a recent epidemiologically based study reported a high rate of ADHD in autism and autism spectrum disorders (ASD). In the planned revision of the DSM-IV TR, dsm5 (www.dsm5.org), the diagnoses of autistic disorder and ADHD will not be mutually exclusive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
185
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(197 citation statements)
references
References 236 publications
7
185
1
4
Order By: Relevance
“…Similarly, studies on maternal autoimmune disorders during pregnancy have reported different associated disorders (psoriasis with ASD; thyroid antibodies with ADHD) [361]. Group B streptococcus (GBS) is the most frequent commensal bacterium colonizing or infecting pregnant women.…”
Section: Prenatal Risk Factorsmentioning
confidence: 99%
“…Similarly, studies on maternal autoimmune disorders during pregnancy have reported different associated disorders (psoriasis with ASD; thyroid antibodies with ADHD) [361]. Group B streptococcus (GBS) is the most frequent commensal bacterium colonizing or infecting pregnant women.…”
Section: Prenatal Risk Factorsmentioning
confidence: 99%
“…The Childhood Autism Rating Scale (CARS) is used extensively in clinical environments to evaluate severity of autism based on observation of children in autism [27][28][29] . A pediatricians usually perform a preliminary analysis by taking the developmental record and physically examining the child.…”
Section: Diagnosis Of Autismmentioning
confidence: 99%
“…If warranted, evaluations and diagnosis are conducted with assist from autism specialists, observing and assessing communication, cognitive and family. Differential identification for autism at this phase might also consider mental retardation, hearing impairment, and specific language impairment 27 .…”
Section: Diagnosis Of Autismmentioning
confidence: 99%
“…However, it is not uncommon to have overlapping symptoms of ADHD and ASD in one child, such as deficits in attention, behavioral problems and social difficulties and several studies demonstrated that about 20% -50% of children with ADHD meet the diagnostic criteria for ASD and about 30% -80% of children with ASD meet the diagnostic criteria for ADHD (Mattila et al, 2010;Rommelse, Franke, Geurts, Hartman, & Buitelaar, 2010). There have been debates, over the last decade about overlapping symptoms and comorbidity of ASD and ADHD (Ames & White, 2011;Gargaro, Rinehart, Bradshaw, Tonge, & Sheppard, 2011;Reiersen & Todd, 2008;Ronald, Simonoff, Kuntsi, Asherson, & Plomin, 2008;Taurines et al, 2012), leading to acceptance of dual diagnosis of ASD and ADHD in DSM-5 (APA, 2013).…”
Section: Introductionmentioning
confidence: 99%